AI-Enhanced Optimization Techniques for MicroStrip Antenna Design: A Comparative Study - Swapna Mudey (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Advancements in telecommunication require antenna systems that are more efficient, cost-effective, and compact. Conventional design approaches for microstrip antennas sometimes have difficulties in meeting these strict requirements because of their inherent limits in dealing with intricate optimisation problems that involve several, frequently contradictory, design objectives. This research article investigates the capacity of artificial intelligence (AI) to surpass these restrictions by utilizing sophisticated optimization techniques to improve micro strip antenna designs. The paper specifically does a comprehensive comparative examination of three main AI-based optimisation methodologies: Genetic Algorithms (GA), Particle Swarm Optimisation (PSO), and Deep Learning (DL) techniques. The efficacy of these AI-augmented methodologies is assessed using various performance criteria essential to antenna design, including as gain, bandwidth, radiation pattern, and size reduction. Commercially available electromagnetic simulation software was utilised to conduct a series of simulations. This software allowed for the modelling and optimisation processes to be carried out under controlled and repeatable settings. The application of each methodology was conducted on a standard microstrip antenna design problem, and the results were thoroughly examined to evaluate the influence of each artificial intelligence method on the performance and efficiency of the design. The robustness of Genetic Algorithms in global optimisation and their capability to handle discrete and multi-objective issues were investigated. The simplicity and efficiency of Particle Swarm Optimisation in converging on an optimal solution with minimal parameter adjustments were assessed. The predictive capabilities of deep learning, namely convolutional neural networks, were investigated in order to automate the design process by learning from past design iterations. The findings demonstrated that GA (Genetic Algorithm) and PSO (Particle Swarm Optimisation) had a notable impact on improving the antenna's bandwidth and gain. On the other hand, DL (Deep Learning) methods outperform in automating and fine-tuning the design process, resulting in a reduction in the time required for the design cycle. Furthermore, deep learning models have shown an impressive capability to accurately forecast the most suitable antenna characteristics, hence enabling a more intuitive approach to design. This study concludes that the integration of artificial intelligence (AI) into microstrip antenna design can both shorten the design process and greatly improve the performance parameters. The comparative analysis offers profound insights into the effective utilisation of each AI technique in various scenarios of antenna design, paving the way for the development of more intelligent, AI-driven design tools in the field of telecommunication engineering. This study establishes a basis for future research, in which more intricate AI models could be created and perhaps incorporated into real-time design procedures for diverse applications in telecommunications and other fields.